IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE FOR SUSTAINABLE BUSINESS IN BUMDES IN BOGOR DISTRICT - Hari Gursida; Didik Notosudjono; Yohannes Indrayono; Hendro Sasongko (Rural Development For Economic Resilience (RUDENCE), 2023)
ABSTRACT There are quite a number of Village-Owned Enterprises (BUMDES) in the Bogor Regency area. However, of the number of BUMDES there are still a few whose business conditions are in the developing and advanced category. By looking at this condition, community service activities are aimed at providing ways, namely how to apply good business governance for sustainable businesses, especially for BUMDes that are in the developing and advanced category, so that their business can be sustainable. The method of implementing community service is carried out by first determining which BUMDES are in the developing and advanced category, identifying BUMDES problems, classifying BUMDES problems, analyzing and providing solutions and their implementation. The results of this activity BUMDES must apply governance in the fields of finance, human resources, and taxation in a good and consistent manner so that the business runs in a sustainable manner. ABSTRAK Jumlah Badan Usaha Milik Desa (BUMDES) cukup banyak di wilayah Kabupaten Bogor. Namun, dari jumlah BUMDES masih ada beberapa yang kondisi usahanya masuk kategori berkembang dan maju. Dengan melihat kondisi tersebut, kegiatan pengabdian kepada masyarakat ditujukan untuk memberikan cara-cara, yaitu bagaimana menerapkan tata kelola usaha yang baik bagi usaha yang berkelanjutan, khususnya bagi BUMDes yang berada dalam kategori berkembang dan maju, sehingga usahanya dapat berkelanjutan. Metode pelaksanaan pengabdian kepada masyarakat dilakukan dengan terlebih dahulu menentukan BUMDES mana yang masuk kategori berkembang dan maju, mengidentifikasi permasalahan BUMDES, mengklasifikasikan permasalahan BUMDES, menganalisis dan memberikan solusi serta pelaksanaannya. Hasil dari kegiatan ini BUMDES harus menerapkan tata kelola di bidang keuangan, sumber daya manusia, dan perpajakan secara baik dan konsisten agar usaha berjalan secara berkelanjutan.